Evaluation of oxygenated n-butanol-biodiesel blends along with ethyl hexyl nitrate as cetane improver on diesel engine attributes. (10th January 2017) - Imdadul, H.K.; Masjuki, H.H.; Kalam, M.A.; Zulkifli, N.W.M.; Kamruzzaman, M.; Shahin, M.M.; Rashed, M.M.
Abstract: In the present investigation, an attempt has been made to study the fuel properties, engine performance and emission of a diesel engine by mixing ethyl hexyl nitrate (EHN) with n -butanol-diesel-biodiesel blends. The engine test was carried out at full throttle opening in a single cylinder direct injection diesel engine. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) analysis was done to evaluate the thermal properties of the test fuels. Experimental results revealed that the density, viscosity, and other properties are developed well. Notably, the cetane number of the blends increased 4.74% to 11.82% are promising. Alcohol along with cetane improver make the diesel-biodiesel blends thermally more strong. Moreover, introducing the EHN in the blends increased the carbon monoxide (CO) up to 16.64%, hydrocarbon (HC) emissions up to 27.46%, brake power (BP) up to 5.62% and brake thermal efficiency (BTE) up to 2.5% compared to the n -butanol added biodiesel blends. On the other hand, the brake specific fuel consumption (BSFC), nitric oxide (NO) and smoke reduced from 1.44% to 2.8%, 2.53% to 5.27% and 7.08% to 14.11% respectively with the addition of EHN into the n -butanol mixed biodiesel blends. Hence it can be concluded that the addition of cetane improver to oxygenated alcohol treated biodiesel blends is well efficient for a diesel engine. Highlights: Thermal stability of the modified blends increased. Cetane number of the EHN treated blends improved. NO and smoke emission decreased for EHN treated blends. EHN addition increase the HC and CO emission. BP, BSFC and BTE improved as oxygenated alcohol and EHN added.